Education Leadership: Legal and Social Impacts of Public Schools Leadership and Management on the City of Baltimore Maryland, United States of America - Anucha, Hyacinth (Advances in Social Sciences Research Journal, 2023)
This study assessed the correlation between per student expenditure and academic achievement, examining legal issues, poverty, and crime as chronic factors impacting low academic performance as parents’ legal actions against the City School Board of Commissioners question the effectiveness of public school spending. Ineffective leadership, mismanagement, poverty, and crime contribute to subpar performance, necessitating new strategies for learning, teaching, and meeting high academic standards. The Baltimore City public school system has faced challenges in academic achievement, poverty, and crime over the past decades. Maryland’s Blueprint for the Future and meta research emphasize the importance of effective leadership and quality education to enhance student achievement, socioeconomic growth, and reduce crime. The present research analyzed various factors influencing public school performance, including per teacher and pupil expenditure, while correlating SAT and ACT scores with academic improvement in Baltimore City, Maryland. Besides, it is declared that effective educational leadership is imperative in a data driven culture whose challenges lie not in advanced technology itself but rather in the transformation of repressive cultures, teams, and practices.